PRESERVATIVE MEDIA FOR Beauveria bassiana (BALS.) VUILL STORAGE - MOHAMMAED, HELBEN ISMAT; MIRZA, MOHAMMED SAEED; HASSAN, FEYROZ RAMADAN (Journal of Duhok University, 2020)
Beauveria bassiana is an important entomopathogenic fungus that used as a biocontrol agent of insect pests. Maintaining and preserving B. bassiana cultures is essential for the effective evaluation of its potential as microbial agent against insect pest, for biodiversity studies and also for exchange of fungal material between laboratories. In the present work we evaluated the suitability of four preservation materials based on gelatin and rice to maintain the viability of B. bassiana to be used as baits for insect’s control. The gelatin amended with sugar recorded the maximum viability after 70 days of storage as 98.3% compared to 63.3% on rice media. Effective control of 80% of the ants was observed after 10 days of feeding on gelatin amended with sugar and rice bait. The results demonstrated that treatment with formulations containing conidia of B. bassiana presents insecticidal activity against ant in addition of acting as preservation materials.